The relationship between authentic leadership and athlete burnout: A longitudinal study - Fu, Y.; Li, C.; Peng, Y.; Chen, R.; Deng, G.; Hu, C. (Journal of Sports Sciences, 2025)
Athlete burnout is a significant psychological and behavioural issue in the athletic domain. Authentic leadership, an emerging leadership style characterised by self-awareness, transparency, moral behaviour, and balanced processing, may hold potential value in mitigating athlete burnout. However, longitudinal research exploring the reciprocal relationship between authentic leadership and athlete burnout at the individual level remains scarce, particularly regarding the underlying mechanisms, such as psychological capital and empathy . Empirical studies on these pathways are still insufficient. In this study, researchers adopted a longitudinal design and constructed a Random Intercept Cross-Lagged Panel Model (RI-CLPM) and a Linear Mixed Model (LMM) to examine the relationship between authentic leadership and athlete burnout from both intra-individual and interpersonal perspectives. From March 2024 to November 2024, a total of 441 athletes (Mage = 20.28, SD = 2.08) completed three waves of assessments. The results indicated that: (a) authentic leadership and athlete burnout were bidirectionally related; (b) authentic leadership indirectly predicted athlete burnout through psychological capital; and (c) empathy moderated the relationship between psychological capital and athlete burnout. These findings provide longitudinal empirical evidence for the reciprocal influence between authentic leadership and athlete burnout and offer new theoretical insights into the psychological regulation processes of individuals in competitive sports. .